Characterization, recombinant production and structure-function analysis of NvCI, a picomolar metallocarboxypeptidase inhibitor from the marine nnail Nerita versicolor - Covaleda Cortes, Giovanni (2019)
A very powerful proteinaceous inhibitor of metallocarboxypeptidases has been isolated from the marine snail Nerita versicolor and characterized in depth. The most abundant of four, very similar isoforms, NvCla, was taken as reference and N-terminally sequenced to obtain a 372-nucleotide band coding for the protein cDNA. The mature protein contains 53 residues and three disulphide bonds. NvCIa and the other isoforms show an exceptionally high inhibitory capacity of around 1.8 pM for human Carboxypeptidase A1 (hCPA1) and for other A-like members of the M14 CPAsubfamily, whereas a twofold decrease in inhibitory potency is observed for carboxypeptidase B-like members as hCPB and hTAFIa. A recombinant form, rNvCI, was produced in high yield and HPLC, mass spectrometry and spectroscopic analyses by CD and NMR indicated its homogeneous, compact and thermally resistant nature. Using antibodies raised with rNvCI and histochemical analyses, a preferential distribution of the inhibitor in the surface regions of the animal body was observed, particularly nearby the open entrance of the shell and gut, suggesting its involvement in biological defense mechanisms. The properties of this strong, small and stable inhibitor of metallocarboxypeptidases envisage potentialities for its direct applicability, as well as leading or minimized forms, in biotechnological/biomedical uses.